The Effect of Giving A Warm Blanket to Changes in The Central Temperature of Postoperative Patients with Subarachnoid Block Anesthesia in RSSA Malang - Djatmi Ekorini; Sih Ageng Lumadi (Jurnal Keperawatan, 2021)
Introduction: Shivering after anesthesia subarachnoid block is a common complication seen with an incidence of 40-60% after anesthesia. One of the post pharmacological shivering management is given a warm blanket. Experimental research was carried out in the Conscious Installation Room of the Central Surgical Installation of RSSA Malang. Aims: The purpose of this study was to determine the effect of providing warm blankets on changes in the central temperature of postoperative patients with subarachnoid block anesthesia. The benefits of this study are to improve the quality of care for patients with surgery, accompanied by shivering events. Methods: The research design was Quasy-Experiment with Random Sampling technique, and the sample size was 20 respondents, two groups: control and treatment. The two groups of respondents' temperature were evaluated and noted before treatment and after giving blankets every 15 minutes to 60 minutes. Result: The test results of the average temperature difference before treatment and the second 60 minutes of the two groups p = 0.0142 with α = 0.05 showed significant differences concluded that temperature changes in post-anesthesia patients subarachnoid block. Conclusions: Non-pharmacological hypothermia treatment after anesthesia subarachnoid block using an electric blanket warmer is more effective because the blanket's temperature can be maintained stable so that the heat transfer process does not decrease the temperature the blanket due to the temperature of the cold environment.